Regional financial performance mediates the effect of regional balance funds and expenditures on economic growth - Dilliana, Siktania Maria; Gayatri, Gayatri; Ratnadi, Ni Made Dwi; Wirajaya, I Gde Ary (International research journal of management, IT and social sciences, 2019)
This study aims to obtain empirical evidence about the balance funds and regional expenditure on economic growth with regional financial performance as a mediating variable. The results showed that the balance fund did not affect the financial performance of the region with a result of 0.054 indicating that the balance fund received by the regional government increased or decreased could not affect the regional financial performance. Regional expenditure has a negative effect on regional financial performance with a result of 0.006 indicating that the allocation of indirect expenditure is higher than the direct expenditure allocation. Balancing funds have a positive effect on economic growth with a result of 0.031 indicating that the amount of general allocation funds, special allocation funds, and profit-sharing funds has increased so that economic growth also increases. Regional expenditure has a positive effect on economic growth with a result of 0.020` indicating that there is infrastructure development undertaken to encourage regional economic growth. Regional financial performance has a positive effect on economic growth with a result of 0.009 indicating that regional capability is getting better based on the results of the ratio of independence, effectiveness, and efficiency.